Modularity of Orthopedic Implants 1997
DOI: 10.1520/stp12034s
|View full text |Cite
|
Sign up to set email alerts
|

Fretting Corrosion Mechanisms at Modular Implant Interfaces

Abstract: Modular connections have been commonly and successfully utilized in orthopaedic implant systems for the last 15 or so years, particularly at the head/neck junction in total hip arthroplasty (THA). However, recent retrieval studies have shown that some of the tapered junctions between femoral heads and stems in total hip arthoplasty can be prone to fretting corrosion, and may be a cause for concern in the longevity of implants. Fretting corrosion, which may release metallic products (particulate debris and ions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…It is known that design variables such as head diameter, head offset, material combination and taper angles have a significant effect on taper debris generation in THRs (Bone et al, 2015;Jani et al, 1997;Langton et al, 2012;Schmidt et al, 1997). There is inevitable variability in the manufacturing tolerances for the taper and trunnion cone angles of these THRs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that design variables such as head diameter, head offset, material combination and taper angles have a significant effect on taper debris generation in THRs (Bone et al, 2015;Jani et al, 1997;Langton et al, 2012;Schmidt et al, 1997). There is inevitable variability in the manufacturing tolerances for the taper and trunnion cone angles of these THRs.…”
Section: Discussionmentioning
confidence: 99%
“…Brock et al (2015) also showed high volumetric wear rates for the taper of explanted CoCr heads and hypothesised that a rougher taper surface could increase the wear rates at this taper junction. Jani et al (1997) showed that taper variations such as taper design and taper surface finish have a significant impact on the fretting behaviour at the THR taper junction. Femoral head offsets are also known to likely have an effect on the generation of wear debris at the taper junction (McGrory et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, fretting corrosion may occur also at backside contacts in joint prostheses, bone-implant contact regions, overlapping cardiovascular stent contact points and other locations where surface contact and small cyclic motion exist [40]. Hence, fretting corrosion of biomaterials and implants has been studied extensively in the lab as well as on retrieved implants [40,68,142,143,271,329,330,331,332,333,334,335,336,337,338,339,340,341,342,343,344,345,346,347,348]. ASTM F1875 [349] specifies fretting corrosion testing of hip femoral head/bore and cone taper interface in modular implants.…”
Section: Mechanisms Of Corrosion In Vivomentioning
confidence: 99%
“…Several in vitro studies have been conducted on cyclically loaded modular prostheses to investigate the effects of mechanical loading on fretting and corrosion 8–23. Many researchers concluded that fretting could lead to corrosion due to disruption of the surface oxide 10, 12, 19, 24, 25.…”
Section: Introductionmentioning
confidence: 99%